2020
DOI: 10.1108/ijilt-02-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Remaking and reinforcing mathematics and technology with programming – teacher perceptions of challenges, opportunities and tools in K-12 settings

Abstract: PurposeThe purpose of this study is to analyse and discuss K-12 mathematics and technology teachers' perceptions on integrating programming in their teaching and learning activities, and perceptions on different programming tools.Design/methodology/approachThe approach of a case study was used, with data collected from three instances of a professional development programming course for K-12 teachers in mathematics and technology.FindingsThe findings show that there are perceived challenges and opportunities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
3
8
0
1
Order By: Relevance
“…Similar results were highlighted in a study that investigated Swedish secondary school teachers' perceptions on integrating programming in Mathematics and Technology courses and of different programming tools (Humble et al, 2020). The study concluded that programming is perceived by many of the teachers as fun but that there is a lack of time and directives for the integration, which the teachers perceived as challenging (Humble et al, 2020).…”
Section: Related Worksupporting
confidence: 60%
See 2 more Smart Citations
“…Similar results were highlighted in a study that investigated Swedish secondary school teachers' perceptions on integrating programming in Mathematics and Technology courses and of different programming tools (Humble et al, 2020). The study concluded that programming is perceived by many of the teachers as fun but that there is a lack of time and directives for the integration, which the teachers perceived as challenging (Humble et al, 2020).…”
Section: Related Worksupporting
confidence: 60%
“…It is further highlighted that there is risk for inequality among schools regarding access to support, professional development, IT infrastructure, and active leadership in the digital transformation (Vinnervik, 2022). Similar results were highlighted in a study that investigated Swedish secondary school teachers' perceptions on integrating programming in Mathematics and Technology courses and of different programming tools (Humble et al, 2020). The study concluded that programming is perceived by many of the teachers as fun but that there is a lack of time and directives for the integration, which the teachers perceived as challenging (Humble et al, 2020).…”
Section: Related Worksupporting
confidence: 53%
See 1 more Smart Citation
“…In fact, previous studies have shown that teachers feel that it is easy to connect programming to other teaching and learning activities in school, such as problem solving. However, sometimes there is a lack of directives for the integration, in terms of what type of programming should be implemented [34]. In this sense, it is important to know Scratch limitations and when another programming language, such as Python, should be used as an alternative.…”
Section: Methodologiesmentioning
confidence: 99%
“…In the UK, computing education has been described as "patchy and fragile" with lack of teacher support (The Royal Society, 2017). Research have further described a lack of time for the integration and challenges for both teachers and students to learn programming (Allison, 2021;Humble, Mozelius & Sällvin, 2020). To address the challenges of integrating programming in K-12 education, this study describes the process of designing, developing, and evaluating an educational game on programming.…”
Section: Introductionmentioning
confidence: 99%